Assessment of Commonly Used Pediatric Stool Scales: A pilot study - M. Saps; D. Nichols-Vinueza; G. Dhroove; P. Adams; A. Chogle (Revista de Gastroenterología de México, 2013)
Background: The Bristol Stool Form Scale (BSFS) and a modified child-friendly version (M-BSFS) are frequently used in clinical practice and research. These scales have not been validated in children. 3-D stool scale models may be better adapted to the child's development. Aims: To assess the usefulness of the BSFS, M-BSFS, and a newly developed 3-D stool scale in children. Methods: Fifty children were asked to rank the picture cards of the BSFS and 3-D models from hardest to softest and to match the pictures with descriptors for each stool type. Results: Thirty percent of the children appropriately characterized the stools as hard, loose, or normal using the BSFS vs. 36.6% with the 3-D model (p=0.27). Appropriate correlation of stools as hard, loose, or normal consistency using the BSFS vs. the 3-D model by age group was: 6 to 11-year-olds, 27.5% vs. 33.3% (p=0.58) and 12 to 17-year-olds, 32.1% vs. 39.5% (p=0.41). Thirty-three percent correlated the BSFS pictures with the correct BSFS words, 46% appropriately correlated with the M-BSFS words, and 46% correlated the 3-D stool models with the correct wording. Conclusions: The BSFS and M-BSFS that are widely used as stool assessment instruments are not user-friendly for children. The 3-D model was not found to be better than the BSFS and the M-BSFS.